Cultural adaptation of the opening minds scale for health care providers(OMS-HC) for Brazil - Carrara, Bruna Sordi; Ventura, Carla Aparecida Arena; Costa, Simone de Godoy (Acta Scientiarum. Health Sciences, 2022)
The Opening Minds Scale for Health Care Providers (OMS-HC) identifies health professionals’ attitudes and behaviors towards people with mental illness. The aim of this study was to culturally adapt the OMS-HC for use in Brazil through the description of the translation and back-translation process, face and content validity assessment, and reliability assessment. The cultural adaptation occurred through translation of the original instrument, assessment, and synthesis of the translation by the Committee of Judges, back-translation, and pre-test. The cultural adaptation occurred without significant intercurrences, the changes resulting from the translations and assessments were, in general, specific and related to the changes of certain words by other synonyms for better adaptation. Cronbach’s alpha was 0.74. The Brazilian version of the OMS-HC presented language adequate to the Brazilian context that is easy to apply, with adequate format for use, appropriate understanding, and consistency in relation to the original version. The Brazilian version of the OMS-HC is suitable for the development of a study to assess its psychometric properties.